United States - Venezuela relations during the Trump government. Between a radical discourse, economic pragmatism and the sanctions cudgel - Bodemer, Klaus (2023)
Based on the central importance of oil in the Venezuelan economy and politics, as well as the consequent dependence of the Andean country on the US —its main oil buyer— this paper takes stock of the bilateral relations between both countries, particularly during the years of the Donald Trump administration. Lacking an articulated strategy, the North American government applied a policy of sanctions that failed in its main objective: the fall of Chavismo and a regime change. The causes of failure are multiple and are due to both internal and external factors. In our analysis we will use the categories of social constructivism and two levels game, respectively.